2022
DOI: 10.3389/fpubh.2022.975992
|View full text |Cite
|
Sign up to set email alerts
|

What is the quality of life in patients with long COVID compared to a healthy control group?

Abstract: IntroductionMany patients have prolonged symptoms after COVID-19 infection, which can affect patient quality of life (QOL). The aim of this study is to determine the quality of life in patients with long COVID, compared with healthy controls.Material and methodsThe study was a prospective cross-sectional study using an anonymous online survey. The SF-36 questionnaire was chosen for quality of life measurement. The survey was distributed through the Facebook social media platform targeting groups of patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 57 publications
0
37
0
1
Order By: Relevance
“…Long-COVID can affect multiple systems including cardiovascular, pulmonary, metabolic, coagulation and hematologic, renal, gastrointestinal, musculoskeletal, neurologic, and psychiatric disorders, with significant impacts on morbidity and mortality ( 1 4 ). A recent study also reported a significantly lower quality of life for Long-COVID patients compared to a healthy control group ( 5 ). Ongoing low-grade inflammation has been hypothesized to cause these symptoms, but the pathology remains largely unknown, knowledge on the best tools for its evaluation and diagnosis is still incomplete, and treatments are primarily based on symptoms relief.…”
Section: Introductionmentioning
confidence: 90%
“…Long-COVID can affect multiple systems including cardiovascular, pulmonary, metabolic, coagulation and hematologic, renal, gastrointestinal, musculoskeletal, neurologic, and psychiatric disorders, with significant impacts on morbidity and mortality ( 1 4 ). A recent study also reported a significantly lower quality of life for Long-COVID patients compared to a healthy control group ( 5 ). Ongoing low-grade inflammation has been hypothesized to cause these symptoms, but the pathology remains largely unknown, knowledge on the best tools for its evaluation and diagnosis is still incomplete, and treatments are primarily based on symptoms relief.…”
Section: Introductionmentioning
confidence: 90%
“…The COVID-19 pandemic has led to a signi cant number of cases of Long COVID syndrome, which can persist for months and substantially impact patients' quality of life [3] . Treatment of Long COVID can be challenging, and existing options have had limited success [20,27] . This is the rst multicenter, double-blind, intervention study assessing the quality of life in Long COVID patients, and we have demonstrated that the dietary supplement EchA Marine® can signi cantly enhance the quality of life of these patients, particularly as regards pain and discomfort; notably improving their quality of life and ability to have a better mobility.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the EuroQol has proven to be a valuable tool for assessing quality of life in a wide range of medical conditions and appears to be particularly useful for assessing the quality of life in patients with Long-COVID-19 [9,16,17] . With speci c reference to Long-COVID, the EuroQol has been able to detect the decrease in health-related quality of life and has been able to demonstrate that Long COVID involves a signi cantly higher disability rate than that which is seen in the general population [9,18,19,20] .…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms can be diverse and commonly include nonspecific neurological and neuropsychiatric symptoms including difficulty concentrating or subjective ‘brain fog,’ unusually profound fatigue, headaches, depression, anxiety, body pain, and disrupted sleep (Davis et al, 2021; Zeng et al, 2023). These symptoms can significantly impact quality of life (Líška et al, 2022), and can be initiated even by mild acute COVID-19 illness (Boribong et al, 2022; Ma et al, 2023).…”
Section: Introductionmentioning
confidence: 99%